Current treatment strategies targeting histone deacetylase inhibitors in acute lymphocytic leukemia: a systematic review - Zhang, Yingjun; Zhang, Ge; Wang, Yuefang; Ye, Lei; Peng, Luyun; Shi, Rui; Guo, Siqi; He, Jiajing; Yang, Hao; Dai, Qingkai (Frontiers in Oncology, 2024)
Acute lymphocytic leukemia is a hematological malignancy that primarily affects children. Long-term chemotherapy is effective, but always causes different toxic side effects. With the application of a chemotherapy-free treatment strategy, we intend to demonstrate the most recent results of using one type of epigenetic drug, histone deacetylase inhibitors, in ALL and to provide preclinical evidence for further clinical trials. In this review, we found that panobinostat (LBH589) showed positive outcomes as a monotherapy, whereas vorinostat (SAHA) was a better choice for combinatorial use. Preclinical research has identified chidamide as a potential agent for investigation in more clinical trials in the future. In conclusion, histone deacetylase inhibitors play a significant role in the chemotherapy-free landscape in cancer treatment, particularly in acute lymphocytic leukemia.